Australotarsiusa new genus of the rove beetle tribe Staphylinini from Australia (Coleoptera: Staphylinidae: Staphylininae) - Solodovnikov, Alexey; Newton, Alfred F. (Zootaxa, 2009)
Australotarsius Solodovnikov & Newton, gen. nov., a new genus of rove beetles of the tribe Staphylinini, endemic to Australia, is described and compared to other Staphylinini. It includes two new species, A. grandis Solodovnikov & Newton, sp. n. from Queensland and New South Wales, and A. tasmanicus Solodovnikov & Newton, sp. n. from Tasmania. The systematic position of Australotarsius within Staphylinini needs further investigation in the context of a broad-scale phylogenetic study of this large tribe. Preliminarily this new genus is thought to be a member of the lineage of Staphylinini which includes genera Anchocerus Fauvel, 1905, Acylophorus Nordmann, 1837, Anaquedius Casey, 1915, Hemiquedius Casey, 1915 and possibly Euryporus Erichson, 1839, all of which are current members of the subtribe Quediina.